BIHAR SPECIAL LIBRARIES ELECTRONIC RESOURCES AND SERVICES: AN ANALYTICAL STUDY - Ashok Kumar (International Journal of Multidisciplinary Research and Studies, 2021)
IT applications and the reinvention of existing applications, and the process of organisational innovation, which consists of the actual adoption and implementation of an IT application in an organisation, the use of these applications, and the effect that this has on the work and communication in the organisation. The use of information technology in organisations is a dynamic interaction between these two processes. Libraries get "material" from many different sources in many different formats. Although the catalogues of the library have traditionally been the tool for searching for information owned by the library, catalogues typically do not include the capability of searching at the article level for materials that have appeared in magazines, journals, newspapers, and other collected works. While the catalogues have traditionally been the tool for searching for information owned by the library, this is no longer the case.